A Meta-analysis of the effect of integrated Traditional Chinese and Western medicine on abdominal distention and constipation after surgery for thoracolumbar fracture (中西医结合治疗胸腰段骨折术后腹胀便秘疗效的Meta分析) - SUN Haichao (孙海超); YAO Yufei (姚雨菲); WANG Yuejuan (王月娟); WEI Jinrong (魏金荣) (中西医结合护理)
Objective To evaluate the clinical effect of integrated Traditional Chinese and Western medicine on abdominal distention and constipation after surgery for thoracolumbar fracture. Methods The CNKI, CBM, VIP and Wanfang Date databases were searched by computer. Randomized controlled trials (RCTs) on the efficacy of integrated Traditional Chinese and Western medicine in the treatment of abdominal distention and constipation after surgery for thoracolumbar fracture were included. RevMan 5. 4 software was used for data analysis from database construction to March 2022, and Jadad scale was used to evaluate the literature quality and funnel plot was used to analyze whether there were publication offset results in the included literature. Results After screening, 7 literatures were included, including 590 subjects: 301 in the experimental group and 289 in the control group. Meta-analysis showed that the nursing measures of integrated Traditional Chinese and Western medicine were significantly better than conventional nursing measures in treating and relieving postoperative abdominal distention and constipation(P＜0. 05). Conclusion Based on the current clinical evidence, the full application of the dialectical theory of traditional Chinese medicine and the adoption of appropriate Chinese medicine prescriptions combined with routine orthopedic nursing measures can effectively relieve the symptoms of abdominal distension and constipation in patients with thoracolumbar fracture after surgery, relieve discomfort and improve nursing satisfaction, which can provide clinical reference (目的 通过Meta分析系统评价中西医结合治疗胸腰段骨折术后腹胀便秘的临床效果。方法 计算机检索中国知网(CNKI)、中国生物医学文献库(CBM)、维普数据库(VIP)和万方数据(Wanfang Data)数据库, 纳入中西医结合治疗胸腰段骨折术后腹胀便秘疗效的随机对照试验(RCTs), 选取文献时间从建库至2022年3月。采用RevMan 5. 4软件进行数据分析、Jadad量表对文献质量进行评价、漏斗图分析纳入的文献是否存在发表偏移。结果 经筛选后最终纳入7个文献, 共590人, 试验组301人, 对照组289人。Meta分析结果表明中西医结合的护理措施在治疗和缓解患者术后腹胀便秘的症状明显优于常规护理措施(P＜0. 05)。结论 基于目前临床证据表明, 充分应用中医辨证论治理论, 采用合适的中药方剂结合骨科护理常规等措施, 能有效缓解胸腰段骨折术后患者腹胀便秘症状, 减轻不适感, 提高护理满意度, 可为临床提供参考。)